Applications and Future Potential of X-ray Diffraction in Pharmaceutical Polymorphism: A Literature Review - Dwiputra, Rizki Rava; Saputri, Jasmine Rahma; Utami, Marsah Rahmawati (Indonesian Journal of Chemistry and Environment, 2024)
Polymorphism in drug compounds is a significant phenomenon in pharmacy because it affects physicochemical properties such as solubility, stability, and bioavailability, which impact the effectiveness and safety of drugs. X-ray diffraction (XRD) is one of the methods that can be used to identify and analyze the polymorphic properties of drug compounds. This article reviews the utilization of XRD in various studies, showing that this method is effective for identifying polymorphism, detecting changes in crystal forms, monitoring crystalline phase transitions, and characterizing the formation of new crystalline phases. Although very useful, XRD has limitations in detecting amorphous phases and requires optimal sample preparation. For more comprehensive results, XRD is often combined with other techniques such as DSC and FTIR. Overall, XRD plays an important role in drug development and quality control, and this technology is expected to continue evolving, including its ability to directly monitor the crystallization process to enhance drug quality and stability.